(untitled) (Annals of Medical Research, 2021)
Aim: The first COVID-19 case in Turkey was detected on March 11, 2020 during the COVID-19 pandemic process. Epidemiological studies are needed to be prepared for other outbreaks and to be effective in the disease management process. Based on this reason, in this study it was aimed to determine the epidemiological characteristics of Covid 19 possible and definite cases who applied to the university hospital during the pandemic process. Materials and Methods: This retrospective epidemiological study was carried out by analyzing the data of Covid 19 possible and definite cases, who applied to the university hospital operating as a pandemic hospital between 11 March / 01 June 2020. The data were summarized with descriptive statistics, tables and graphs. Results: Of the 1,383 patients, who applied with the suspicion of COVID-19, 55.5% were men and 84.5% were adults. The median age of children is 4.0 (1.5-10) years old; adults were 52.0 (36.0-67.0) years old. The median time between the outset of complaints and the date of admission to the hospital was 2 (1-3) days. 87.4% of adults and 87.9% of children had symptoms that supported COVID-19 infection. Among cases 7.8% were health care workers. The median age of the fatal cases was 71 (64-82) years old, 79.5% were male, 77.7% were retired. The most common comorbide diseases in these cases were hypertension (28.2%) and malignancy (28.2%). The case fatality rate was found as 2.8% in all patients and 48.4% in patients hospitalized in the intensive care unit. Conclusions: As a result, Covid-19 affects all age groups. Hypertension and malignancy were the most common additional diseases in fatal cases. The risk of illness is higher in healthcare workers who have direct contact with the patients. According to our observations, preventive measures, rapid diagnosis and supportive treatment are valuable.